A III‐nitride polarization enhanced electron filter for controlling the spectral response of solar‐blind AlGaN/AlN/SiC photodiodes. Issue 3 (27th February 2014) - Rodak, L. E.; Sampath, A. V.; Gallinat, C. S.; Smith, J.; Chen, Y.; Zhou, Q.; Campbell, J. C.; Shen, H.; Wraback, M.
Abstract: Heterogeneous aluminium gallium nitride (Al x Ga1‐ x N)/aluminium nitride (AlN)/silicon carbide (SiC) based n‐i‐p photodetectors have been demonstrated to effectively tailor the spectral response of SiC within the solar‐blind regime. The differences in polarization at the hetero‐interfaces resulting in negative polarization induced charge at the Al x Ga1‐ x N/AlN interface and positive polarization induced charge at the AlN/SiC interface has been exploited to create a large barrier to carrier transport across the interface. This barrier impedes the collection of photo‐excited holes in the Al x Ga1‐ x N layers and enables the selective collection of electrons photo‐excited to the Γ and L conduction band valleys of SiC while blocking the collection of electrons in the M valley. In this work, the influence of device design, including the AlN layer thickness and Al x Ga1‐ x N composition, on the spectral response is discussed. Thin AlN barrier layers are easily overcome by electrons generated in all valleys of 4H‐SiC with increasing bias voltage while thicker barrier layers successfully minimize the collection of electrons in the M valley of SiC and therefore suppress the long‐wavelength response >260 nm. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)